Exploring Organic Food Supply Chains: Trends and Sustainability (Journal of Asian Development Studies, 2023)
The focus of this study is to deal with organic food supply chain by examining the roles of its key stakeholders (farmer, processor, wholesaler, retailer and consumer) through a systematic literature review from 2011 to 2022. Organic food has gained substantial global demand due to health-conscious consumers gravitating towards natural, pesticide-free, and chemical-free food. In contrast, conventional food production has often prioritized profitability over health, resulting in quality control issues. Organic food, however, places a premium on quality and meticulous processes. The study identifies critical research questions, investigating the significant contributions, characteristics, state-of-the-art research, and future directions in organic food supply chains. Through systematic review methodology, this study analyzed 139 papers published from 2011 to 2021. It revealed an increasing trend in organic food research, with top journals like the Journal of Cleaner Production leading the discourse. Italy emerged as the chief publishing country, with China being a prominent funding agency. The primary research methods employed included case studies and modelling, with the logistics and farming sectors of the supply chain receiving the most attention. This research offers a comprehensive overview of the organic food supply chain and its key actors, shedding light on critical research areas and trends, which can guide future studies and further the advancement of sustainable organic food supply chains.